Эпидемиологические особенности распространенности, формирования и выявления фенотипов артериальной гипертензии в популяции неорганизованного населения пожилого и старческого возраста: 31-летнее наблюдение - Каландаров, Дилмурод; Мамасалиев, Неъматжон; Мамасалиев, Зохиджон; Мирсайдуллаев, Мирмахмуд; Мамасалиева , Шахноза (Профилактическая медицина и здоровье, 2025)
Arterial hypertension, hypertensive disease, hypertensive state, hypertensive crisis, and the associated hypertensive continuum are among the most important medical, social, and economic problems of the healthcare system, as ..."all population groups worldwide are affected by this pandemic..." A direct or indirect (through their risk factors) relationship between the pre-hypertensive state/arterial hypertension and remodeling of the cardiovascular system has been proven in clinical and experimental studies. In Uzbekistan, the provision of quality cardiological medical services to the population has been fundamentally improved, and modern methods for effective treatment of cardiovascular diseases and pre-hypertensive conditions are being implemented. However, despite specific measures taken in healthcare, there are currently urgent and problematic issues, including in the field of preventive cardiology/hypertensiology, awaiting solutions at the regional level. On an international scale, targeted scientific work is being consistently carried out to study the origin and epidemiology of arterial hypertension, its regional formation in various population groups through more in-depth prospective studies, as well as to identify/distinguish the role of risk factors in its development mechanism. Such studies primarily cover important medical preventive and pharmacotherapeutic areas such as comprehensive analysis of disease causative factors in hypertensive conditions, demonstrating the preventive-diagnostic significance of numerous risk factors in its early detection, or assessing the interrelationship between general and regional risk factors and epidemiological indicators of hypertensive conditions. At the same time, research on introducing new regionally significant and effective preventive diagnostic methods based on general epidemiological patterns and risk factors, early detection of hypertensive conditions, and modifying and developing individual (regional) approaches to their treatment/control is of great importance.